The function of NOD2 in antigen presenting cells - Allan, P (2012)
Crohn’s disease (CD), a chronic inflammatory condition of the gut affecting 1:1000 of western populations, is thought to arise from a dysregulated immune response in a genetically susceptible individual. Polymorphisms in the ligand recognition domain of an intracellular pattern recognition receptor (PRR), NOD2, remain the strongest genetic risk factor for the development of CD. NOD2 directs autophagy in human DCs to facilitate bacterial destruction and antigen presentation; the CD-variant-NOD2 shows defects in this pathway. Recent work in the laboratory has demonstrated NOD2 signals to control expression induction of microRNA-29, which is impaired in cells from CD patients expressing CD NOD2-variants, and among other immunoregulatory effects, microRNA-29 suppresses IL-12p40/IL-23. Thus NOD2 directs key anti-microbe and immunoregulatory functions whose breakdown in the presence of CD-variant-NOD2 could act as a trigger for inflammation in this disease. In comparison with other PRRs, relatively little is understood of the hardwiring of NOD2 signalling, the mechanism of NOD2-mediated autophagy induction, the means by which NOD2 recruits a signalling platform within the cytosol and the mechanism of synergy with other PRRs and the inflammasome. In this work I used quantitative proteomics to map the NOD2 signalling cascade and its cross-talk with TLR2, demonstrating novel mediators: LCP1, a plastin, reduced phagocytosis of bacteria but did not alter bacterial killing, and aided control of the release of MCP1 and may be involved in IL-12p40 release. SHP1, a phospho-tyrosine phosphatase, is required for the propagation of signalling cascades via p38, p44/42 MAPK and NF-κB. It controls release of MIP1β and IL-12p40. HMGB1, an alarmin, is dephosphorylated on NOD2 stimulation and would result in changes to cellular location of HMGB1. Lastly, DAPK1, a serine/threonine kinase, is associated with HLA-DM loading compartment on NOD2 triggering, but does not alter CLIP levels on the surface of the cells. Thus, defining the hard wiring of NOD2 signalling in healthy donors, in comparison with CD donors expressing variant NOD2, is important to define targets amenable to drug design within this pathway.